Current cancer stem cell biomarkers in laryngeal cancer - Karatas, Omer Faruk; Barlak, Neslisah; Sahin, Huseyin; Aydin, Hatice (The European Research Journal, 2017)
Larynx cancer (LCa), being an aggressive malignancy, is the second most commonly diagnosed malignant type of head and neck squamous cell carcinoma worldwide. Although there have been significant improvements in the detection and diagnosis of LCa in the last decades, it is still one of the considerable causes of cancer deaths and an urgent need for identification of novel biomarkers with diagnostic and prognostic significance still remains. The cancer stem cells (CSCs) resemble normal stem cells in terms of biological features and are considered to play critical roles in biological aggressiveness of tumors. Accumulating evidences have proven the existence of CSCs in various tumors including LCa and they are considered as driving force for tumor relapse, metastasis, and chemo-radioresistance. Comprehensive identification and characterization of the CSCs is of paramount importance for their further characterization to develop more effective and targeted therapeutic strategies against cancer. Here, we reviewed and summarized the most current literature to provide an insight into the functions and roles of current CSCs biomarkers in human LCa. We believe that this review will contribute to the knowledge of scientists especially working with LCa CSCs and will help understanding the significance of CSCs biomarkers implicated in LCa pathogenesis.